2000
DOI: 10.1097/00000478-200011000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal-Type Fibroma in Two Related Patients With Gardner's Syndrome

Abstract: Nuchal-type fibroma is a distinct subcutaneous and dermal fibrous tissue proliferation that has been previously definitely identified in one patient with Gardner's syndrome and has been possibly present in two others. Gardner's syndrome is an autosomal-dominant condition with variable expressivity that comprises epidermoid cysts, fibrous tumors, osteomas, intestinal polyposis, as well as other findings. We report two cases of nuchal-type fibroma presenting in a 13-year-old boy in the right upper back and in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 17 publications
0
39
1
Order By: Relevance
“…The tumor typically presents between the third and fifth decades of life, but lesions have additionally been reported in patients aged 3-74 years. Nuchal-type fibroma has been observed to be strongly associated with diabetes mellitus and Gardner's syndrome (12). There is a ratio of 4:1 male to female predominance, although this is not observed in Gardner's syndrome-associated patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor typically presents between the third and fifth decades of life, but lesions have additionally been reported in patients aged 3-74 years. Nuchal-type fibroma has been observed to be strongly associated with diabetes mellitus and Gardner's syndrome (12). There is a ratio of 4:1 male to female predominance, although this is not observed in Gardner's syndrome-associated patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…1 Other spindle cell neoplasms associated with CD34 expression include cases of sclerotic fibromas, nuchal fibromas, solitary fibrous tumors, cellular blue nevi, nerve sheath tumors, stromal cells surrounding trichoepitheliomas, and Kaposi sarcoma [1][2][3][4][5] (Table II).…”
mentioning
confidence: 99%
“…It suggests that nuchal-type fibroma with diabetes may occur by tumor-like changes in fibrous tissues, like a link between diabetes and scleredema. And, some authors suggested by their case reports that nuchal-type fibroma is related to Gardner's syndrome [7][8][9] . Gardner syndrome, caused by mutations in the adenomatous polyposis coli (APC) gene, is characterized by polyposis coli, osteomas, and various soft-tissue tumors.…”
Section: Discussionmentioning
confidence: 99%